2017
DOI: 10.1063/1.4995566
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction using wrinkled surfaces in high Reynolds number laminar boundary layer flows

Abstract: Inspired by the design of the ribbed structure of shark skin, passive drag reduction methods using stream-wise riblet surfaces have previously been developed and tested over a wide range of flow conditions. Such textures aligned in the flow direction have been shown to be able to reduce skin friction drag by 4 − 8%. Here, we explore the effects of periodic sinusoidal riblet surfaces aligned in the flow direction (also known as a "wrinkled" texture) on the evolution of a laminar boundary layer flow. Using numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 40 publications
5
53
1
Order By: Relevance
“…SA5 Surface area, Volume.Crown5 Volume of the crown, SA.Crown5 Surface area of the crown, Volume.Base5 Volume of the base, SA.Base5 Surface area of the base, Volume.CB Ratio5 Ratio of the volume of the crown to the volume of the base, PerVolC Ratio5 Ratio of the volume of the crown to the volume of the whole denticle. -Ardakani & McKinley, 2017). We discuss issues relating to denticle ridges and fluid dynamics in more detail below, but here we note that our measurements of the height and spacing of mid-body ridges on six species of sharks showed that smooth dogfish and shortfin mako sharks are the most similar (Tables 2 and 5) while species such as spiny dogfish and leopard sharks have relatively widely spaced and higher ridges on the surfaces of denticles.…”
Section: Comparison Of Denticle Structure Among Body Locationsmentioning
confidence: 85%
See 1 more Smart Citation
“…SA5 Surface area, Volume.Crown5 Volume of the crown, SA.Crown5 Surface area of the crown, Volume.Base5 Volume of the base, SA.Base5 Surface area of the base, Volume.CB Ratio5 Ratio of the volume of the crown to the volume of the base, PerVolC Ratio5 Ratio of the volume of the crown to the volume of the whole denticle. -Ardakani & McKinley, 2017). We discuss issues relating to denticle ridges and fluid dynamics in more detail below, but here we note that our measurements of the height and spacing of mid-body ridges on six species of sharks showed that smooth dogfish and shortfin mako sharks are the most similar (Tables 2 and 5) while species such as spiny dogfish and leopard sharks have relatively widely spaced and higher ridges on the surfaces of denticles.…”
Section: Comparison Of Denticle Structure Among Body Locationsmentioning
confidence: 85%
“…Shark denticle ridges (often termed riblets by analogy to engineered ridge‐like structures) have been the subject of considerable focus due to their possible association with fluid dynamic drag reduction and both biologists and engineers have focused intensively on the spacing of ridges (e.g., Bechert, Bruse, & Hage, ; Motta et al, ; Raayai‐Ardakani & McKinley, ). We discuss issues relating to denticle ridges and fluid dynamics in more detail below, but here we note that our measurements of the height and spacing of mid‐body ridges on six species of sharks showed that smooth dogfish and shortfin mako sharks are the most similar (Tables and ) while species such as spiny dogfish and leopard sharks have relatively widely spaced and higher ridges on the surfaces of denticles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one observation from the Figure 9 is that the critical Reynolds number decreases for the increases of the roughness. For example the critical Reynolds number for single start is around 1.4×10 5 and gradually decreases for higher number of starts and for 6 starts the critical Reynolds number is found around 4×10 4 . Similar findings are also obtained by Adachi [22] and Hojo [23].…”
Section: Same Pitch With Different Number Of Startsmentioning
confidence: 96%
“…It is well-known that the drag in a cylinder decreases when the wake behind it changes laminar flow with turbulent including a narrow wake width. RaayaiArdakani and McKinley [5] includes wrinkled surface and show that the surface texture can be able to reduce the skin friction drag. Massumoto et al [6] proposed apple shape geometry and compared with sphere and different hollow shaped geometries like U-shaped, Vshaped grooves and find that apple shape geometry can reduce the drag up to 23% as compared with sphere and 13% with circular cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Among a number of boundary layer controlling devices such as suction [2,3], blowing [4], synthetic jets [5], vortex generators [6], and riblets [1,[7][8][9][10][11][12], riblets are one of the methodologies used to reduce aircraft surface drag [1,[7][8][9][10][11][12]. Riblets are a passive means of turbulent flow control by which skin friction drag is reduced, and were first employed at the NASA Langley Research Center back in the 1970s [8,13] in imitation of the skin structure of a shark that swims long distances at high speed.…”
Section: Introductionmentioning
confidence: 99%